The Tale of Two Bad Mice - Potter, Beatrix (Penguin Group, 1996)
While the dolls are away, two curious, naughty mice explore the dolls' house and steal their furniture.
Keywords: Animals; Juvenile Fiction; Mice, Hamsters, Guinea Pigs